Pengaruh Mekanisme Internal Corporate Governance Terhadap Pemilihan Auditor Eksternal - Febrina Nafasati P; Dian indu dewi (Universitas Semarang, 2019)
Internal Coporate Governance Mechanism influence for Auditor Choice. The research is to know of the impact of Internal Corporate Governance Mechanism on auditor choice by non-financial companies, where the proxies of Internal Corporate Governance Mechanism used are the largest shareholder, audit committee’s effectivenese, the number of board of commissioner and the proportion of independent commissioner. This study used Top 4-non Top 4 auditor segregation as a proxy of auditor quality that will be chosen by the company.This study used Logistic Regresion and used 177 of non financial companies listed on the Indonesia Stock Exchange 2013. The Result showed that there are significant of the number of board of commissioner and audit committee’s effectivenese on auditor choice by company. Therea are not significant of the largest shareholder and the proportion of independent commissioner on auditor choice by company.